Increased iron level in phytase-supplemented diets reduces performance and nutrient utilisation in broiler chickens. Issue 4 (4th July 2017) - Akter, Marjina; Iji, P. A.; Graham, H.
ABSTRACT: 1. The effect of different levels of dietary iron on phytase activity and its subsequent effect on broiler performance were investigated in a 3 × 2 factorial arrangement. A total of 360 day-old Ross 308 male broiler chicks were distributed to 6 experimental diets, formulated with three levels of Fe (60, 80 and 100 mg/kg) and two levels of phytase (0 and 500 FTU/kg). 2. Phytase supplemented to mid-Fe diets increased feed consumption more than the non-supplemented diet at d 24. From hatch to d 35, Fe × phytase interaction significantly influenced the feed intake (FI), body weight gain (BWG) and feed conversion ratio (FCR). The high-Fe diet supplemented with phytase significantly reduced FI and BWG of broilers than those supplemented with low- or mid-Fe diets. The overall FCR was significantly better in birds fed on the mid-Fe diets with phytase supplementation. 3. A significant improvement in ileal digestibility of N, P, Mg and Fe was observed in birds feed diets containing 60 mg Fe/kg, with significant interaction between Fe and phytase. 4. Phytase improved the bone breaking strength when supplemented to low- or mid-Fe diets, compared to the non-supplemented diets. There was a significant Fe × phytase interaction effect. Tibia Fe content was higher in birds fed on phytase-free diets with high Fe but the reverse was the case when phytase was added and their interaction was significant. High dietary Fe significantly increased the accumulation of Fe in liver. 5. Phytase improved Ca-Mg-ATPase, Ca-ATPase and Mg-ATPase activities in jejunum when supplemented to the diet containing 80 mg Fe/kg. 6. This study indicates that high (100 mg/kg) dietary Fe inhibited phytase efficacy and subsequently reduced the overall performance and nutrient utilisation of broilers.